The other person’s smiling amount affects one’s smiling response during face-to-face conversations - Obayashi, Yota; Uehara, Shintaro; Yuasa, Akiko; Otaka, Yohei (Frontiers in Behavioral Neuroscience, 2024)
Introduction Smiling during conversation occurs interactively between people and is known to build good interpersonal relationships. However, whether and how much the amount that an individual smiles is influenced by the other person’s smile has remained unclear. This study aimed to quantify the amount of two individuals’ smiles during conversations and investigate the dependency of one’s smile amount (i.e., intensity and frequency) on that of the other. Method Forty participants (20 females) engaged in three-minute face-to-face conversations as speakers with a listener (male or female), under three conditions, where the amount of smiling response by listeners was controlled as “less,” “moderate,” and “greater.” The amount of the smiles was quantified based on their facial movements through automated facial expression analysis. Results The results showed that the amount of smiling by the speaker changed significantly depending on the listener’s smile amount; when the listeners smiled to a greater extent, the speakers tended to smile more, especially when they were of the same gender (i.e., male–male and female–female pairs). Further analysis revealed that the smiling intensities of the two individuals changed in a temporally synchronized manner. Discussion These results provide quantitative evidence for the dependence of one’s smile on the other’s smile, and the differential effect between gender pairs.